Implementation of User-Centered Design in Online Seminar Application - Meida Cahyo Untoro (STEKOM PRESS, 2020)
Online seminars have many benefits in various fields of science. Information about workshops online, registration, and other activities so that it can help users get information. During the pandemic, COVID-19 had a strategic role in providing information related to the development of science and insight. The right application will provide optimal data and information to all users. The online seminar application is designed with a User-centered design to obtain user-friendly information and usability. The results of the study showed that the online seminar application that was designed had good usability and was acceptable to users. usability testing concluded that an acceptable application with a value of 82.40% and block box testing received the designed menu.